Associations of maternal early-pregnancy dietary glycemic index with childhood general, abdominal and ectopic fat accumulation - Wahab, Rama J. (Clin Nutr, 2021)
BACKGROUND & AIMS: Maternal hyperglycemia during pregnancy is an important risk factor for childhood adiposity. Maternal dietary glycemic index during pregnancy directly influences maternal and fetal glucose concentrations. We examined the associations of maternal early-pregnancy dietary glycemic index with offspring general, abdominal and ectopic fat accumulation among normal weight and overweight or obese pregnant women and their offspring. METHODS: In a population-based cohort study among 2488 Dutch pregnant women and their children, we assessed maternal dietary glycemic index by food frequency questionnaire at median 13.4 (95% range 10.7; 21.1) weeks gestation. Dietary glycemic index was used continuously and categorized into low (≤55), normal (56–69) and high (≥70) glycemic index diet. We measured offspring BMI, total fat mass and android/gynoid fat mass ratio by DXA, and visceral fat mass and liver fat fraction by MRI at 10 years. RESULTS: No associations of maternal early-pregnancy dietary glycemic index with offspring adiposity were present among normal weight women and their children. Among overweight and obese women and their children, 1-Standard Deviation Score (SDS) increase in maternal early-pregnancy dietary glycemic index was associated with higher childhood BMI (0.10 SDS, 95% Confidence Interval (CI) 0.01; 0.19), total fat mass index (0.13 SDS, 95% CI 0.05; 0.22), visceral fat mass index (0.19 SDS, 95% CI 0.07; 0.32) and tended to be associated with a higher android/gynoid fat mass ratio (0.09 SDS, 95% CI −0.01; 0.19) and higher risk of childhood overweight (Odds Ratio (OR) 1.20, 95% CI 0.97; 1.48). Overweight and obese women consuming an early-pregnancy low-glycemic index diet, as compared to an early-pregnancy normal-glycemic index diet, had children with lower BMI, total fat mass index, visceral fat mass index and android/gynoid fat mass ratio at 10 years (p-values<0.05). No women consumed a high-glycemic index diet. No associations were explained by maternal socio-economic, lifestyle and dietary characteristics, birth or childhood characteristics. No associations with liver fat fraction were present. CONCLUSIONS: In overweight or obese women and their children, a higher maternal early-pregnancy dietary glycemic index is associated with childhood general, abdominal and visceral fat accumulation, but not with liver fat. Intervention studies among overweight and obese pregnant women may need to target the dietary glycemic index to prevent childhood adiposity.